UJI PALATABILITAS TEPUNG BUNGKIL KELAPA SAWIT YANG DIHIDROLISIS DENGAN ENZIM RUMEN DAN EFEK TERHADAP RESPON PERTUMBUHAN BENIH IKAN PATIN SIAM (Pangasius hypophthalmus Sauvage) - Wahyu Pamungkas (Research Center for Biology-Indonesian Institute of Sciences, 2013)
The quality of feed is not only determined by the nutrient content and digestibility of the feed or feed ingredients, but also determined by the palatability of the feed. Palatability is one of important factor in the preparation of rations, because palatability affects the amount of feed intake. The purpose of the study was to determine the effect of feed commercial mixed with palm kernel meal (PKM) that was hydrolyzed by sheep rumen liquor enzyme to palatability of feed by measuring total feed consumption and growth responses of seed catfish (Pangasius hypopthalmus Sauvage). The feeds used in the study were commercial feed added hydrolyzed palm kernel meal (PKMe) and unhydrolized palm kernel meal (PKM). The treatments were as follows A). Commercial feed, B). 30% + 70% BKSecommercial feed30% PKMe + 70% commercial feed, C). 40% PKMe + 60% commercial feed, D). 30% PKM + 70% commercial feed, E). 40% PKM+ 60% commercial feed. Ten fishes with wight around 20 g were used in the trial and held in 80 l tanks. A completely randomized experimental design consisted of 1 variable and triplicates were selected. The result of the experiment showed that feed consumption was not significantly different among the treatment. It was showed that the test diet have a good palatability. The result of feed consumption, survival rate and growth responses observation showed that it was not significantly different among the treatments (P>0.05). Result of digestibility analysis showed that diet A and B have digestibility coefficient higher than diet C and D. Based on the evaluation in those parameters it was concluded that palm kernel meal that has been hydrolized by sheep rumen liquor enzyme have a good palatability and can be used as feed for seed catfish (Pangasius hypophthalmus Sauvage) with addition of up to 40% in the feed.